1989
DOI: 10.1002/jso.2930400409
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of survival in patients with unresectable colorectal liver metastases

Abstract: Prognostic indicators in 67 patients with unresectable colorectal liver metastases were analyzed. These patients were identified to have isolated hepatic metastases after extensive radiological evaluation and demonstrated good performance status without evidence of liver failure. Univariate analysis revealed 6 of 22 factors that were associated with survival: alkaline phosphatase (AP), lactic dehydrogenase (LDH), occult intra-abdominal extrahepatic disease, percent hepatic replacement by tumor (PHR), sex, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
3

Year Published

1991
1991
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 19 publications
1
14
3
Order By: Relevance
“…Moreover, temporary, nonprogressive elevations of CEA were seen in 30% of patients, which is an extreme example of this phenomenon (Rittgers et al, 1978). Despite the lack of specificity for colon cancer, CEA demonstrated an excellent correlation in patients with colorectal liver metastases (Chu et al, 1982;DeBrauw et al, 1987;Lorenz et al, 1989;Chang et al, 1989). Our study confirms these findings with 100% score.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, temporary, nonprogressive elevations of CEA were seen in 30% of patients, which is an extreme example of this phenomenon (Rittgers et al, 1978). Despite the lack of specificity for colon cancer, CEA demonstrated an excellent correlation in patients with colorectal liver metastases (Chu et al, 1982;DeBrauw et al, 1987;Lorenz et al, 1989;Chang et al, 1989). Our study confirms these findings with 100% score.…”
Section: Discussionsupporting
confidence: 83%
“…Other significant factors influencing survival were found to be ALP [34,36,44], SGOT [44], 5' Nt 1451, LDH [24], and PS [24,38]. As was previously stated, it is believed that liver function tests reflect the extent of liver involvement, although other investigators showed that these variables were independent prognostic factors [45].…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have reported the prognostic significance of LDH in patients with metastatic colorectal cancer (Chang et al, 1989;Kemeny et al, 1989;Steinberg et al, 1992;Fountzilas et al, 1996). Indeed, one study (Kemeny & Braun, 1983) described the importance of LDH as an independent predictor of survival in advanced colorectal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Other prognostic factors for colorectal cancer include age, tumor grade, tumor size and location, symptom duration, and vascular and neural invasion. More recently, other prognostic factors have been identified including carcinoembryonic antigen (CEA), carbohydrate antigen 19-9 (CA 19-9), serum albumin, alkaline phosphatase, lactate dehydrogenase (LDH), aspartate aminotransferase, gamma-glutamyl-transpeptidase, and performance status (Chang et al, 1989;Kouri et al, 1992;Steinberg et al, 1992;Wang et al, 2002;Yuste et al, 2003).…”
Section: Introductionmentioning
confidence: 99%